Literature role in the daily Malay community in the novel "Seorang Tua Di Kaki Gunung From the Perspective Theory of Pengkaedahan Melayu" - Ishak, Nadia; Kamarudin, Kamariah; Mohd. Hanafiah, Halis Azhan; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2021)
If enlightened the place of literature in the lives of Malay community, literature and the Malay communities are the two components that cannot be separated. Literature plays a role to upgrade the mind-set of the community in every aspect. Meanwhile, through literature communities enhance its well -being in daily life on morality towards civilization. Literature is a feeling within the soul of the author which is than translated and written out to spread on the reality happenings in human lives. Therefore, this case study is a research to literary work on how literature plays the role in the Malay community life. This research is an under lie on the novel of the Seorang Tua di Kaki Gunung (1982) authored by Azizi Haji Abdullah using the theory of Pengkaedahan Melayu as an analytical framework. This theory is by Hashim Awang, emphasizing on the ways of living, faith and the cultural of Malay Muslim community. This research data is compiled based on qualitative study and content analysis as the main instrument research. In summary, this research shows the important roles of literature in the daily Malay community life in absorbing all the principle through the theory of Pengkaedahan Melayu.